2013
DOI: 10.1021/mp400122m
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Paclitaxel and Rapamycin Individual and Dual Drug-Loaded Polymeric Micelles in the Angiogenic Cascade

Abstract: Angiogenesis is an essential process for disease progression in many solid tumors. There are several major cascade events in the angiogenic process that can be targeted to inhibit new blood vessel formation in the tumor tissue. The purpose of this work is to evaluate the inhibitory effect of paclitaxel (PTX) and rapamycin (RAP) as individual and in dual drug-loaded poly(ethylene glycol)-block-poly(d,l-lactic acid) (PEG-b-PLA) micelles on the angiogenic cascade processes of proliferation, migration, and tube fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…The amphiphilic copolymers have also demonstrated better loading capacity for the encapsulated drugs. Mishra et al have encapsulated PTX and rapamycin (RAPA) into PEG-b-PLA for synergistic antitumor therapy [103]. To increase the cellular uptake efficiency, chitosan was also used as a material for surface functionalization of NPs.…”
Section: Nanoformulation-mediated Co-delivery Of Small-molecule Chmentioning
confidence: 99%
“…The amphiphilic copolymers have also demonstrated better loading capacity for the encapsulated drugs. Mishra et al have encapsulated PTX and rapamycin (RAPA) into PEG-b-PLA for synergistic antitumor therapy [103]. To increase the cellular uptake efficiency, chitosan was also used as a material for surface functionalization of NPs.…”
Section: Nanoformulation-mediated Co-delivery Of Small-molecule Chmentioning
confidence: 99%
“…Thus, in the case of MIX-M the tumor volume reduction is also driven by the inhibition of the angiogenesis, while in the case of the individual micelles, at these concentrations only angiogenesis inhibition occurs but no cytotoxic effects are seen. The ability of PTX and RAP to induce an antiangiogenic effect is well documented in the literature and many studies have shown that the endothelial cells and neovasculature are sensitive to these agents at concentrations lower than that required for cancer cells 18,22,33 . Clearly the PTX-M and RAP-M follow the same pattern at 20 mg/kg to produce antiangiogenic effects without apoptosis induction in the tumor tissue.…”
Section: In Vivo Efficacy Studies In Es2 Murine Xenograft Modelmentioning
confidence: 99%
“…The treatment groups in both experiments were HUVEC left untreated (control), treated with 0.2 nM of PTX, RAP in individual micelles or 0.1 nM of each in MIX-M. PTX-M and RAP-M concentrations selected for the studies were below the IC 50 values in HUVEC of the micelles (Fig.5). This selection was based on earlier findings that PTX and RAP inhibit endothelial migration and tube formation at much lower doses than their IC 50 33,70 . Data from the migration assay is presented in Fig.…”
Section: In Vitro Real-time Migration and Tube Formation Studies In Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, antineoplasic drugs used in conjunction within a single formulation/delivery system are not commercially available so far [10]. The combination of two or more different drugs within one single nanocarrier might help in simplifying tumor treatments, make them much less harmful to patients by allowing: (i) drugs transport to their site of action by passive and/or active mechanisms; (ii) drug protection and avoidance of early clearance from the body; (iii) their sustained and controlled release from the nanocarrier to achieve optimal therapeutic doses in situ; and (iv) the enhancement of their circulation times and the improvement of their pharmacokinetics and pharmacodynamics [11, 12].…”
Section: Introductionmentioning
confidence: 99%